A case of extensive alopecia areata following Pfizer‐BioNTech BNT162b2 mRNA COVID‐19 vaccine with favorable outcome - Yoshihiro Matsuda; Yoshio Kawakami; Masaya Kawamoto; Yoji Hirai; Shin Morizane (Frontiers Media S.A., 2023)
A 37‐year‐old woman developed persistent low‐grade fever (37.2°C) on day +13 after the first dose of BNT162b2 mRNA vaccine. She noticed coin‐sized hair loss on day +22, and it became widespread within 1 week. The patient's hair mostly recovered leaving only one oval bald patch on day +310 with topical corticosteroid therapy alone.